2022
DOI: 10.1093/plphys/kiac015
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase 1/GSK3/SHAGGY-like kinase 2/BRASSINAZOLE-RESISTANT 1 module controls lateral root formation in rice

Abstract: Lateral roots (LRs) are a main component of the root system of rice (Oryza sativa) that increases root surface area, enabling efficient absorption water and nutrients. However, the molecular mechanism regulating LR formation in rice remains largely unknown. Here, we report that Histone Deacetylase 1 (OsHDAC1) positively regulates LR formation in rice. Rice OsHDAC1 RNAi plants produced fewer lateral roots than wild-type plants, whereas plants overexpressing OsHDAC1 exhibited increased lateral root proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…HDAs play vital roles in the negative regulation of transcriptional expression during different developmental processes and environmental stress signaling in plants. [42][43][44][45][46][47] Due to the transcriptional reprogramming by HDAs, the involvement of HDAs in plant stress responses has been widely reported in model plants (Arabidopsis, rice, etc.). [45][46][47][48][49][50] Here, this study not only identifies MeHDA9 as a novel regulator of cassava disease resistance, but also illustrates the direct relationship between MeHDA9-mediated histone deacetylation and melatonin biosynthesis in immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HDAs play vital roles in the negative regulation of transcriptional expression during different developmental processes and environmental stress signaling in plants. [42][43][44][45][46][47] Due to the transcriptional reprogramming by HDAs, the involvement of HDAs in plant stress responses has been widely reported in model plants (Arabidopsis, rice, etc.). [45][46][47][48][49][50] Here, this study not only identifies MeHDA9 as a novel regulator of cassava disease resistance, but also illustrates the direct relationship between MeHDA9-mediated histone deacetylation and melatonin biosynthesis in immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45][46][47] Due to the transcriptional reprogramming by HDAs, the involvement of HDAs in plant stress responses has been widely reported in model plants (Arabidopsis, rice, etc.). [45][46][47][48][49][50] Here, this study not only identifies MeHDA9 as a novel regulator of cassava disease resistance, but also illustrates the direct relationship between MeHDA9-mediated histone deacetylation and melatonin biosynthesis in immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modulating the function of various HDACs can have different effects on rice growth and development. Overexpression of OsHDA702 increases the number of lateral roots on primary roots (Hou et al, 2022), while oshda703 plants showed pleiotropic phenotypes, including delayed growth, short spikes, erect leaves, and reduced flag leaf angle at the mature stage (Wang et al, 2020). oshda705 and oshda714 mutants also exhibited multiple phenotypes (Xu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, HDACs are classified into three main families: RPD3/HDA1 (homologous to yeast Rpd3p [Reduced Potassium Dependency3]), Sir2 (homologous to yeast Sir2p [Silent Information Regulator2]), and HD2 (plant‐specific HDACs) (Pandey et al, 2002). HDACs regulate gene transcriptional patterns during development and in response to biotic and abiotic stresses (Ding et al, 2012; Luo et al, 2012; Bourque et al, 2016; Hou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%